British Society Reflected in The World of Downton Abbey - Váňa, David (Univerzita Pardubice, 2021)
The aim of this bachelor's thesis is to analyse British society and provide reflection in the Downton Abbey TV series. The thesis is divided into four chapters. Each chapter consists of a theoretical and practical part. The first chapter of the thesis focuses on gender stereotypes and its reflection in various spheres of Edwardian Britain. The second chapter provides insight into sexuality and its understanding in Edwardian England. The third chapter is dedicated to the social structure of Edwardian England. In the third chapter, all three (lower, middle and upper) class are mentioned and compared from various perspectives. Since Downton Abbey is entrenched in popular culture, the thesis elaborates on the Downton TV series from this perspective as well.
Odraz britské společnosti v díle Panství Downton
Keywords: edwardiánská Anglie; stereotypy; sexualita; The New Woman; společenské vrstvy; populární kultura; Edwardian England; stereotypes; sexuality; The New Woman; social classes; popular culture